SOSIALISASI BAHASA INGGRIS MELALUI QUESTION AND ANSWER GAME BAGI SISWA SMA DI KABUPATEN ENDE - Waldetrudis Mbewa; Maria Yulita C. Age (LPPM Institut Pendidikan Nusantara Global, 2025)
The objective of this community service initiative is to promote the use of question-and-answer games in English language instruction to enhance students' listening, speaking, reading, and writing skills. The implementation method involves conducting observations, creating draft questions or initial assessments, designing task distribution for the PkM team, implementing English language proficiency improvement through question-and-answer games, developing follow-up plans, summarizing activity outcomes, and preparing a final report. The results achieved by the students showed that they were very enthusiastic about learning English through games. The question and answer game strengthened the students' English skills (speaking, reading, writing, and listening), language elements such as vocabulary, pronunciation, and grammar, motivation, interest, and active involvement in using English. This educational exercise can inspire students to use English with greater confidence while also creating a fun learning environment. This socialization also motivated teachers at the three partner locations to create variations in media and models to enhance more quality and creative learning